River basin management and the quality of surface water: a case of the Linggi river basin, Negeri Sembilan, Malaysia - Hamirdin Ithnin, (Environmental Management Society, Malaysia, 2001)
The Linggi river basin in Negeri Sembilan in Malaysia covers an important area due to the fact that it is heavily populated. The surface water carried by the main river in the basin, that is the Linggi River, is an important water supply source to the areas around Seremban, Nilai, and Port Dickson. River basin management has not been given an important consideration in the basin such that sources of pollution are found in many places in the basin. This study investigates the river basin management in the area and relates it to the quality of the surface water. It was found that where the river basin management conserves the exploitation of the area, the surface water quality was good. Measure of the water quality was based on the Water Quality Index of the Department of Environment Malaysia. The surface water quality was found to be worse in areas where management of the environment was lax, such as in areas of piggery activities. At the point of intake where raw water is supplied to the Sungai Linggi Water Treatment plant, surface water quality was just slightly out of the much polluted category. The key parameters correlate fairly strongly with urbanized land use, where BOD5 has an R value of 0.71, SS (suspended sediment) 0.65 and NH3N was 0.56. It is suggested that there should be a more meaningful river basin management practice in order to improve the quality of its surface water